Updating a clinical Knowledge-Based Planning prediction model for prostate radiotherapy. (March 2023) - Scaggion, Alessandro; Fusella, Marco; Cavinato, Samuele; Dusi, Francesca; El Khouzai, Badr; Germani, Alessandra; Pivato, Nicola; Rossato, Marco Andrea; Roggio, Antonella; Scott, Anthony; Sepulcri, Matteo; Zandonà, Roberto; et al.
Highlights: Three-years long continuous update and maintenance process of a KBP model for prostate treatments. Two different approaches of KBP update. Practical suggestions for conducting a maintenance process of KBP models to ensure quality of outcomes and model robustness. The process proposed are oriented to be used in the everyday clinical routine of medical physicist. Abstract: Background and purpose: Clinical knowledge-based planning (KBP) models dedicated to prostate radiotherapy treatment may require periodical updates to remain relevant and to adapt to possible changes in the clinic. This study proposes a paired comparison of two different update approaches through a longitudinal analysis. Materials and methods: A clinically validated KBP model for moderately hypofractionated prostate therapy was periodically updated using two approaches: one was targeted at achieving the biggest library size ( Mt ), while the other one at achieving the highest mean sample quality ( Rt ). Four subsequent updates were accomplished. The goodness, robustness and quality of the outcomes were measured and compared to those of the common ancestor. Plan quality was assessed through the Plan Quality Metric (PQM) and plan complexity was monitored. Results: Both update procedures allowed for an increase in the OARs sparing between +3.9 % and +19.2 % compared to plans generated by a human planner. Target coverage and homogeneity slightly reduced [−0.2 %;−14.7 %] while plan complexity showed only minor changes. Increasing the sample size resulted in more reliable predictions and improved goodness-of-fit, while increasing the mean sample quality improved the outcomes but slightly reduced the models reliability. Conclusions: Repeated updates of clinical KBP models can enhance their robustness, reliability and the overall quality of automatically generated plans. The periodical expansion of the model sample accompanied by the removal of the unacceptable low quality plans should maximize the benefits of the updates while limiting the associated workload.